FtsZ phosphorylation modulates tail-core binding to tune cell division in Bacillus subtilis - William J. Mallard; Vincent V. Pham (PLoS ONE, 2025)
The cell division protein FtsZ contains an intrinsically disordered C-terminal tail whose function remains poorly understood. Here we demonstrate that this tail serves as an autoinhibitory element through intramolecular interaction with FtsZ’s globular core. In Bacillus subtilis , we show that FtsZ’s tail is phosphorylated at serine 333 by the kinase PrkC during vegetative growth. We establish that the tail binds specifically to the core’s C-terminal polymerization surface through a molecular recognition element spanning L330-H337. Using NMR spectroscopy, we reveal that phosphorylation of S333 induces structural collapse of the I334-K335 motif, sequestering these key residues from their binding sites and disrupting the tail-core interaction. Mutations at S333 reduce the critical concentration for polymerization and enhance GTPase activity in vitro while altering cell length in vivo . Competition experiments demonstrate that tail-core binding occludes the division inhibitor MinC from the polymerization surface, with S333 mutations restoring MinC binding. Our findings reveal that FtsZ’s tail gates access to the polymerization surface for other FtsZ monomers as well as regulatory proteins, with phosphorylation serving as a molecular switch that coordinates licensing of division regulators and FtsZ polymerization dynamics during the cell cycle.